Interstitial duplication of 20q11.22q13.11: A case report and review of literature. Issue 8 (16th July 2021) - Goetzinger, Logan; Starks, Rachel D.; Dillahunt, Kyle; Major, Heather; Nagy, Jaime M.; Sidhu, Alpa
Abstract: Background: Reports of interstitial duplication of chromosome 20q11 are rare with only nine published patients to date. Methods: We performed karyotype and chromosomal microarray analysis on a peripheral blood sample for our patient and reviewed the genes in the region to provide genotype–phenotype correlation. Results: Clinical features of the patient include minor dysmorphic facial features, shorthands and feet, bilateral conductive hearing loss, global developmental delay, and behavioral issues with attention deficit hyperactivity disorder. Together with previously published cases of 20q11 duplication, we show that patients with overlapping duplications share a similar clinical phenotype of dysmorphic craniofacial features and developmental delay. Conclusion: We report an 8‐year‐old girl with a 9.1 Mb interstitial duplication of chromosome 20q11.22q13.11. Our observations suggest that a novel duplication syndrome and documentation of similar cases will further help clarify the phenotype. Abstract : We report an 8‐year‐old girl with a 9.1 Mb interstitial duplication of chromosome 20q11.22q13.11. Together with previously published cases of 20q11 duplication, we show that patients with overlapping duplication share a similar clinical phenotype of dysmorphic craniofacial features and developmental delay. These observations suggest a novel duplication syndrome.